Avoiding Mistakes in Understanding the Hadith of Prophet Muhammad SAW with YÅ«suf Qaraá¸ÄwÄ«'s Hermeneutics - Kamarudin, Kamarudin; Sarib, Suprijati; M. Arib, Juhrah; Putra, Sudarmadi; Rahman, Rahman (AL QUDS : Jurnal Studi Alquran dan Hadis, 2023)
This article aims to analyze the methodology for understanding hadÄ«th according to YÅ«suf Qaraá¸ÄwÄ«. This study uses library research methods to analyze data. The primary data are Qaraá¸ÄwÄ«'s work, while the secondary data are books and journal articles relevant to the topic of this study. The results of this study indicate that Qaraá¸ÄwÄ« offers eight steps to understanding hadÄ«th, namely defining hadÄ«th based on the Qur'Än, collecting hadÄ«th thematically, compromising contradictory hadÄ«ths, identifying asbÄb al-wurÅ«d of the hadÄ«th, distinguishing changing and unchanging means, differentiating between the literal and figurative language (majÄz), recognizing the unseen and the real, and confirming the meaning of the words in the hadÄ«th. Some points that must be avoided in interacting with á¹£unnÄh are the interpretation of the ignorant, the deviation of the extremes, and the manipulation of the heretics. Furthermore, the basic principles in interacting with á¹£unnÄh are examining the validity of hadÄ«th based on the scientific principles established by hadÄ«th experts, understanding the editorial hadÄ«th properly according to the language instructions and the context of the hadÄ«th, and ensuring that the matÄn of the hadÄ«th does not conflict with the nÄsh of the Qur'an or other hadÄ«th with a more powerful position